IMPROVING STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT USING GENRE BASED APPROACH (GBA) AT THE EIGHTH GRADE STUDENTS OF SMP ISLAM TERPADU FITRAH INSANI - Siti Masitoh; Dasep Suprijadi (Eltin Journal : Journal of English Language Teaching in Indonesia, 2015)
Based on the phenomena that students have difficulties in writing descriptive text, students could not write because the students do not have any ideas when they areasked to write. So, they need some ways which could help them in writing. The problems in writing can be solved by implementing some strategies in teaching writing. One of approach that teacher can use to help students write a good text is GBA. The main objective of this study is find out if GBA can improve students’ ability in writing descriptive text. The research method used is quantitative research, or more specifically quantitative with one group pretest-posttest design. Pretest was given before the students received treatment and posttest was given after students received the treatment. The sample is one class (VIII Al Quds) in SMP ISLAM TERPADU FITRAH INSANI and test as the instrument. Data analysis shows that the observed value of t  (9.474) is bigger than the critical value of t(2.07). GBA has a significant impact on improving students’ ability in writing descriptive text. The teacher should apply the GBA as the alternative for teaching writing descriptive text.              Keywords: Improving, Writing, Descriptive text, and Genre Based Approach